Improving penaeid-trawl efficiencies via ground gear with tickler chains - Matt K. Broadhurst (Aquaculture and Fisheries, 2021)
Penaeid trawls often have poor ecological efficiencies measured as unwanted bycatches (with high discard mortality) and <100% effectiveness for all penaeids interacting with the ground gear (with some escape mortality). This study investigated the utility of varying ground-chain size (8- vs 10-mm diameter (Ø) stainless-steel chain) and the present or absence of a tickler chain (4-mm Ø) for improving efficiencies an Australian fishery diurnally targeting school, Metapenaeus macleayi and eastern king prawns, Penaeus plebejus. There were no treatment effects on wing-end spread and therefore areas trawled. Irrespective of the tickler chain, increasing the ground-chain Ø reduced catches of total penaeids (by 14%) and jellyfish, Catostylus mosaicus (by 39%)—results speculatively attributed to variation in ground contact and/or a slightly higher footrope in trawls with the 10-mm Ø chain. By comparison, installing the tickler chain had no effect on eastern king prawns, but increased catches of school prawns (by 1.13×) and bycatches of blue swimmer crabs, Portunus armatus (1.52×; a species with a low discard mortality) and jellyfish (1.23×), while reducing bycatches of two species with high discard mortalities: southern herring, Herklotsichthys castelnaui (by 38%) and squid, Uroteuthis sp. (37%). The results were attributed to the tickler chain producing (1) mechanical stimuli that augmented the capture of benthic-orientated school prawns (but not eastern king prawns owing to diel variations in emergence from the substrata), blue swimmer crabs and jellyfish; and (2) visual stimuli that possibly enabled some southern herring and squid to detect the trawl and escape. The data show tickler chains can improve trawl efficiency for penaeids with at least some positive effects on bycatch that should be rationalised in terms of species-specific vulnerabilities to unaccounted fishing mortality.